2019
DOI: 10.1016/j.jweia.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

3D LES simulations of a static and vertically free-to-oscillate 4:1 rectangular cylinder: Effects of the grid resolution

Abstract: Vortex induced vibration (VIV) is an important phenomenon which appears in flexible structures immersed in a moving fluid. This oscillation is self-sustained and self-limited, but VIV might cause fatigue damage and affect the structure's serviceability.In the present study, the aerodynamics of the flow fields around a static and vertically free-to-oscillate 4:1 rectangular cylinder are analysed by means of 3D LES simulations, adopting the OneEqEddy viscosity model. Integral parameters, pressure distributions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, the difference between the peak amplitudes obtained by the two turbulence models, can be explained as the k − ω SST models is an isotropic model, which does not resolve all the turbulent scales, concentrating them and yielding more energetic vortices, affecting the value of the aerodynamic damping. In order to account for the flow three dimensionality and resolution of different turbulent scales, LES simulations have been carried out in a different study, where it was found that the mesh discretisation, both in the spanwise direction and in the xy plane, plays a key role [27].…”
Section: Verification Study and Static Case Resultsmentioning
confidence: 99%
“…Moreover, the difference between the peak amplitudes obtained by the two turbulence models, can be explained as the k − ω SST models is an isotropic model, which does not resolve all the turbulent scales, concentrating them and yielding more energetic vortices, affecting the value of the aerodynamic damping. In order to account for the flow three dimensionality and resolution of different turbulent scales, LES simulations have been carried out in a different study, where it was found that the mesh discretisation, both in the spanwise direction and in the xy plane, plays a key role [27].…”
Section: Verification Study and Static Case Resultsmentioning
confidence: 99%
“…It was suggested that eddies of an integral length scale exceeding this range might stimulate a significantly larger VIV amplitude. Similarly, Álvarez et al [80] also studied the VIV of a 4:1 rectangular cylinder using 3D LESs. They investigated the effects of the grid resolution on the VIV amplitudes determined from free oscillation simulations.…”
Section: (1) Investigations Of Factors That Affect Vivsmentioning
confidence: 99%
“…Different turbulence models, including the Unsteady Reynolds-Averaged Navier-Stokes Simulation (URANS), Detached Eddy Simulation (DES), and Large Eddy Simulation (LES), do not seem to reduce the dispersion in the results. Recent numerical simulation results imply that 3D LESs [6][7][8][20][21][22] or DESs [23][24][25][26][27] are more appropriate in complex three-dimensional flows around a rectangular cylinder. Nonetheless, Zhang [28] compared the performance of eight two-equation RANS models and two sub-grid scale (SGS) LES models in the unsteady flow around a finite cylinder with Re = 20,000.…”
Section: Introductionmentioning
confidence: 99%